CHARACTERIZATION OF THE VEGETATION AND SPECIES FOR RECOVERY OF RIPARIAN FOREST, IJUÍ, RS - Avila, Angela Luciana de (2011)
Riparian forests form ecological corridors and enable the preservation of biodiversity and water resources. The maintenance of these ecological functions often requires the environmental restoration of these ecosystems. Thus, we aimed to characterize the arboreal vegetation and identify species for recovery in areas of riparian forests. The study was conducted in two fragments on the left and right banks of the river Ijuí, in the municipality of Ijuí, RS. The vegetation was inventoried in 10 systematic strips, of lengths from 15-35 m, perpendicular to the river, with a distance of 50 m, which were subdivided into plots of 10 x 10 m, totaling 21, in which were identified and measured all individuals with girth breast height (GBH) ≥ 15cm. Data from the inventory were used in the floristic and structural characterization of vegetation, in a clustering analysis (TWINSPAN) and supplied a basis for the indication of species for recovery. We identified 38 species distributed in 20 families. The three groups formed showed different succession stages. For the environmental recovery of altered areas, with similar environmental characteristics, it is suggested the use of Ateleia glazioviana, Helietta apiculata, Dalbergia frutescens and Parapiptadenia rigida as these facilitate succession. The planting of Eugenia uniflora and Prunus myrtifolia can help in attracting disperser fauna. Cupania vernalis and Pilocarpus pennatifolius may be used for the enrichment of areas in a more advanced stage of forest succession.